Efektivitas Berbagai Dosis Pupuk Phonska Pada Media Tanam Buatan Terhadap Ketersediaan P dan K Tertukar Tanah Serta Hasil Pakcoy - Anggi Rahayu; Raden Sri Tejowulan; Baharuddin Abu Bakar; Mulyati (Journal of Soil Quality and Management, 2023)
Mining activities generally leave infertile residual soil, so a strategy needs to be carried out, namely through artificial planting media (MTB) innovations. The purpose of this study was to determine the fertility rate of MTB, the effect of phonska fertilizer doses on the availability of P and K mixed in soil, growth and yield of Pakcoy and the correlation of the level of correlation regression between the availability of P and K mixed in planting media and the wet body weight of Pakcoy plants. The research method used was the experimental method, with a completely randomized design (CRD) of 8 treatments, as follows: P0 = 5 kg of ex-mining soil without additional treatment (control), P1 = MTB (1.6 kg of ex-mining soil + 1 kg of goat manure + 0.3 kg of rice husk biochar) without phonska, P2 = MTB + 20% phonska, P3 = MTB + 40% phonska. P4 = MTB + 60% phonska. P5 = MTB + 80% phonska, P6 = MTB + 100% phonska, P7 = 5 kg of ex-mining land + 100% phonska. Each treatment was repeated 3 times to obtain 24 experimental pot units. Parameters measured were soil texture, available P, exchangeable K, growth, pakcoy yield and other parameters. The results of this study resulted in an additional dose of Phonska fertilizer of 180 kg per hectare (60% Phonska) giving the best plant growth and yields, namely plant height (18.5 cm), number of leaves (19 strands), and wet chestnut weight of 92.6 grams per polybag . The correlation between available-P and K-exchanged soil and fresh plant weight gave a very strong correlation with a coefficient of determination of 0.99 for available-P and 0.85 for K-exchanged. The addition of goat manure and rice husk biochar can improve soil quality and provide maximum results for the growth and yield of pakcoy and can minimize the use of inorganic fertilizers.